Observations on the longevity, instar durations, fecundity and growth in Alonella excisa (Fischer) (Cladocera : Chydoridae) - Sharma, Sumita; Sharma, B K (The Indian Journal of Animal Sciences, 2012)
Alonella excisa (Fischer) passed through 2 pre-adult and 26 adult instars and indicated mean longevity of 73.4 days under laboratory conditions (at 19Â° - 23Â° C). The gravid instars exhibited uniform clutch sizer (2 eggs/brood) and registered cumulative fecundity of 46.0 eggs. Growth was rapid during pre-adult phase of this cladoceran and 90.6% of total length was attained till tenth instar Adult instars recorded longer durations pre-adult instars.